Agglutinins to bacteria in Crohn's disease. Issue 5 (May 1980) - Matthews, N; Mayberry, J F; Rhodes, J; Neale, L; Munro, J; Wensinck, F; Lawson, G H; Rowland, A C; Berkhoff, G A; Barthold, S W
Abstract : Sera from patients with Crohn's disease were tested for antibodies against organisms which are thought to cause inflammatory bowel disease in animals, or have been implicated in human Crohn's disease. Control sera were collected from healthy individuals and patients with ulcerative colitis. Sera from Crohn's disease and controls failed to agglutinate Clostridium colinum or Campylobacter sputorum subsp. mucosalis and two strains of Mycobacterium paratuberculosis (M26 and M27). Most of the sera agglutinated a Citrobacter freundii variant, Mycobacterium paratuberculosis (M28) and Mycobacterium avium (M41) but Crohn's disease sera did not differ from controls. A complement fixation test against Chlamydia gave more positive reactions in patients with Crohn's disease and colitis than in healthy controls. There was a clear difference between the sera from patients with Crohn's disease and other sera, including ulcerative colitis, in agglutination tests with the commensal coccoid rods of the genera Eubacterium and Peptostreptococcus; in these tests 54% of sera from Crohn's disease were positive compared with 11% in ulcerative colitis and none of the sera from healthy controls. All the results were essentially negative with the exception of those from Eubacterium and Peptostreptococcus and these bacteria merit investigation.